2020
DOI: 10.3892/etm.2020.8891
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of five intraocular lens formulas in eyes with trifocal lens implant

Abstract: Accuracy of intraocular lens (IOL) calculation formulas SRK/T, Hoffer Q, Holladay 1, Haigis and Barrett Universal II were compared in prediction of postoperative refraction for multifocal and implants using a single optical biometry device. The authors included 88 refractive lens exchange and cataract surgeries, with AcrySof IQ PanOptix implant (Alcon Laboratories, Inc.). All eyes were divided into three groups based on axial length (AL), group 1: <22 mm (14 eyes), group 2: 22-24.5 mm (68 eyes) and group 3: >2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“… 20 Another study reported that RPE tended to be within ±0.25 D for most eyes analyzed using the Haigis formula and within ±0.50 D for all eyes analyzed using the Barrett Universal II formula among eyes with an axial length between 22.0 mm and 24.5 mm. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Another study reported that RPE tended to be within ±0.25 D for most eyes analyzed using the Haigis formula and within ±0.50 D for all eyes analyzed using the Barrett Universal II formula among eyes with an axial length between 22.0 mm and 24.5 mm. 21 …”
Section: Discussionmentioning
confidence: 99%
“…20 Another study reported that RPE tended to be within ±0.25 D for most eyes analyzed using the Haigis formula and within ±0.50 D for all eyes analyzed using the Barrett Universal II formula among eyes with an axial length between 22.0 mm and 24.5 mm. 21 In this study, we estimated the preoperative RPE for 180 eyes using three well-known IOL power formulas, including the third-generation SRK/T formula and the fourth-generation Barrett Universal II and Haigis formulas, and compared them with the intraoperative prediction of ORA to determine the most suitable method for IOL power selection in eyes with TFNT lenses. 22 Although the accuracy of the IOL power formulas improved with optimization, the accuracy of refractive prediction for TFNT IOLs was the highest with ORA compared with that calculated using the SRK/T, Barrett Universal II, and Haigis formulas even after optimization of the IOL power formulas.…”
Section: Discussionmentioning
confidence: 99%
“…Among the more modern formulas, the lowest refractive error was reported using SRK/ T [24], with keratometry derived from the 3-mm central zone in the axial map of corneal topography [25]. Recent studies are focused on newer generation formulas, in the attempt to find the one with the greatest accuracy in calculating the IOL power [26][27][28]. One study that evaluated the refractive accuracy of Hoffer Q, SRK/ T, Holladay I, Holladay II, Haigis and Barrett Universal II formulas in eyes with keratoconus, found that, while all formulas tended to have a hyperopic error, the Barrett Universal II formula was the most accurate for mild to moderate disease [29] but further research is needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The refractive inclusion criteria were: Manifest hyperopia up to 6.00 diopter (D) with or without astigmatism up to 5.00 D and spherical equivalent +6.00 D at most. Patients outside these limits were referred for intraocular surgery, either phakic Femtosecond-LASIK outcomes using the VisuMax ® -MEL ® 80 platform for hyperopia and hyperopic astigmatism refractive surgery intraocular lenses or refractive lens exchange, according to patient age and ocular biometric considerations (35)(36)(37).…”
Section: Methodsmentioning
confidence: 99%